Comparison of Physical and Physiological Effects of Continuous and Interval Running Training in Elite Adults - Büyükipekci, Serdar; Bozoğlu, Mustafa Sabir (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: It is known that endurance trainings increase physiological adaptations. However, knowledge on its effects on physical and motor performance is insufficient. Therefore, this study aims to compare the effects of 8-week continuous and interval endurance runs on physical and physiological performance in elite adults. Material and Methods: A total of 18 adult male athletes between the ages of 19-25, consisting of continuous runs (CR) n:9 and interval group (IG) n:9, participated in the study. While the continuous running group (CR) was subject to the continuous running method 3 days a week for 8 weeks, interval running method was used for the other group. Experimental research model, including pre-test and post-test, was used in the study. Body weight measurement, 20-meters speed, vertical and horizontal jump, cooper, balance, sit-reach tests were applied to the athletes participating in the study before and after the training program. Variance and homogeneity of the obtained data were tested, and Independent Samples t test and Paired Samples t tests were used in the analysis of the data. Results: After the interval and continuous running training programs, the change in body weight and Cooper test values before and after the interval training and continuous running groups were found to be statistically significant (p<0.05). It was observed that the changes in the standing long jump, speed, vertical jump, balance and sit-and-reach flexibility test values of the interval training group before and after the training were statistically significant (p<0.05) while the change in the continuous running group was not statistically significant. In addition, it was determined that there was a significant change in the balance post-test values in the interval training group compared to the pre-test values. Conclusion: As a result, it shows that the interval and continuous running training programs applied have positive effects on body weight and endurance, and when interval training and continuous running training programs are compared, interval trainings can be efficient in terms of balance, flexibility, vertical and horizontal jump, and 20-meters speed performances.